Effect of depth and diameter of cylindrical cavity in a plate-type methanol steam reformer on estimated net power of PEMFC. (1st December 2018) - Perng, Shiang-Wuu; Wu, Horng-Wen
Highlights: We enhance reforming performance of a plate-type MSR by cylindrical cavities. We study how depth and diameter of cylindrical cavity affects net power of PEMFC. We study methanol conversion, hydrogen yield and CO of an original plate-type MSR. The original MSR obtains the best augmentation of 22.46% in PEMFC net power. The MSR raises methanol conversion up to 22.65% and hydrogen yield up to 64.52%. Abstract: The plate-type methanol steam reformer (MSR) designed for improving its reforming performance is integrated with proton exchange membrane fuel cells (PEMFCs) regarded as a hopeful miniature power source. This study then uses computational fluid dynamics (CFD) through SIMPLE-C algorithm and Arrhenius form of reaction model to study the reforming performance of a plate-type MSR with the cylindrical cavities installed on the bottom of reformer channels. The influences of depth and diameter of cavities, and heated-wall temperature on reforming performance of reformer and estimated net power output of PEMFC have been examined with the same catalyst and inlet conditions in various flow channels of plate-type MSR. The results display that the installation of cylindrical cavities obviously improves the methanol conversion rate and hydrogen yield of a plate-type MSR. Compared with the traditional plate-type MSR, installing the cylindrical cavities of DC  = 1.4 mm and HC  = 1.5 mm on the plate-type MSR channels leads to the best enhancement in the methanol conversion rate by 22.65% and in the hydrogen yield by 64.52% at Theater  = 250 °C. Moreover, the novel plate-type MSR with the cylindrical cavities of DC  = 1.4 mm and HC  = 1.5 mm acquires the best augmentation of 22.46% in the estimated net power output of PEMFC at Theater  = 250 °C.